Pengembangan Sistem Manajemen Dokumen Elektronik Program Studi Manajemen Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta - Fathurrohman Fathurrohman; Siti Zulaikha; Wahyu Sri Ambar Arum (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2016)
This research aims to develop electronic document management system in department of Management of Education, Faculty of Education, State University of Jakarta. Electronic Document Management System (EDMS) is a digital document management system that aims to organize and manage digital documents. The method used is the research and development by research steps, namely: 1) a preliminary study 2) planning 3) product development 4) trials early stage 5) revision 6) test the final stage 7) revision stage end 8) operational trials 9) final revision 10) implementation. Housed in the department of Management of Education, research is conducted since the date of October 1, 2015 until January 18, 2016. The results of this study indicate that the EDMS implemented in department of Management of Education showed positive results in improving document management. EDMS successfully applied, and must be supported by the planting of a new culture that leads to the concept of an electronic organization (e-Organization).